The Role of Artificial Intelligence in Government Services: A Systematic Literature Review - Hamirul; Darmawanto; Nova Elsyra; Syahwami (Open Access Indonesia Journal of Social Sciences, 2023)
Artificial intelligence (AI) technology has become a significant factor in the transformation of government services around the world. AI has opened up new opportunities for governments to improve their effectiveness, efficiency, and responsiveness in providing services to the public. This study aimed to conduct studies in order to conduct an in-depth review of the role of artificial intelligence in government services. Literature search efforts are carried out by searching on search engines using certain keywords. Articles that match the inclusion criteria are reviewed in depth. AI has become a powerful tool for governments to improve public services, administrative efficiency, and better decision-making. The use of AI in government enables fast data processing and accurate analysis, increases the efficiency of public services, strengthens oversight and law enforcement, and supports strategic planning. However, the challenges that need to be addressed, including data privacy, ethics, and public trust, must be looked at carefully.